Environmental attitudes, environmental problems and party choice. A large-N comparative study. (August 2022) - Papp, Zsófia
Abstract: This study investigates the relationship between environmental attitudes and the 'greenness' of party choice, moderated by exposure to environmental problems such as the incidence of natural disasters and poor air quality. The 'greenness' of party choice is operationalised as the share of environmental policy in the parties' election manifestos. Voting for greener parties is especially important for environmental protection because greener votes are the keys to national, and eventually, global action mitigating the effects of environmental degradation. The analysis relies on the European Social Survey, the World Values Survey, the Manifesto Project Dataset, the EM-DAT dataset, as well as World Bank data, and covers 139 surveys in 38 countries between 1995 and 2016. Multilevel linear models reveal that voters with greener attitudes chose greener parties, as expected. At the same time, exposure to country-level environmental problems decreases the effect of these attitudes by significantly increasing the green vote cast by citizens not particularly concerned with the environment. It seems that non-environmental attitudes are substituted by environmental problems in increasing the 'greenness' of the vote. When people meet bad environmental conditions, they are more willing to take environmental action irrespective of their prior attitudes towards environment protection. This foreshadows an increasing overall emphasis on environmental issues in national party politics as more and more countries are facing the dire consequences of a degrading environment.